PRODUCTION OF KNOWLEDGE IN PROEJA, BRAZIL (2006-2013): A STATE OF THE ART - Antonio Marcos Uchoa; Márcio Adriano Azevedo (Holos, 2016)
This article aims to conduct an initial survey and map the academic production on the theme: National program of professional and basic education integration in the young and adult education mode (Programa Nacional de Integração da Educação Profissional com a Educação Básica na Modalidade de Educação de Jovens e Adultos - PROEJA) from dissertations, theses and articles published from 2006 to 2013. In order to undertake this research, we observed some theoretical and methodological procedures, literature review and documents which delimit this conceptual and historic field with the studies of Moura (2007), Moll (2010) Di Pierro (2010), Romanowski and Ens (2006), and Ferreira (2002). It is a bibliographical study which describes the state of the art about PROEJA in the country, having the word “PROEJA” as the research descriptor and the following analysis indicators: year of publication, the place where the research was performed (with empirical research), institution, type of production, categories of knowledge and keywords. The following sources were chosen as databases: Platform Scielo Brazil, the Public Domain Portal of Theses and Dissertations and the Brazilian Digital Library of Theses and Dissertations (BDTD) of the Brazilian Institute of Information Science and Technology (IBCT). It can be concluded that scientific production in the mentioned area is still shy considering the theoretical and methodological challenges posed by the implementation of PROEJA, and there is still remarkably little research related to aspects such as didactic teaching materials, funding and the relationship with rural education.